2017
DOI: 10.1016/j.ibmb.2017.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Towards an understanding of the molecular basis of effective RNAi against a global insect pest, the whitefly Bemisia tabaci

Abstract: In planta RNAi against essential insect genes offers a promising route to control insect crop pests, but is constrained for many insect groups, notably phloem sap-feeding hemipterans, by poor RNAi efficacy. This study conducted on the phloem-feeding whitefly Bemisia tabaci reared on tomato plants investigated the causes of low RNAi efficacy and routes to ameliorate the problem. Experiments using tomato transgenic lines containing ds-GFP (green fluorescent protein) revealed that full-length dsRNA is phloem-mobi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
90
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(99 citation statements)
references
References 60 publications
5
90
0
4
Order By: Relevance
“…Similarly, no apparent lethal phenotype following V-ATPase A knockdown was observed in Aedes aegypti larvae fed with V-ATPase A dsRNA/chitosan nanoparticles and A. aegypti adults fed with V-ATPase A dsRNA. 40,41 In contrast, reduction in V-ATPase A expression in D. virgifera virgifera, 42 Bemisia tabaci 43 and Tuta absoluta 44 resulted in significant insect mortality.…”
Section: Discussionmentioning
confidence: 98%
“…Similarly, no apparent lethal phenotype following V-ATPase A knockdown was observed in Aedes aegypti larvae fed with V-ATPase A dsRNA/chitosan nanoparticles and A. aegypti adults fed with V-ATPase A dsRNA. 40,41 In contrast, reduction in V-ATPase A expression in D. virgifera virgifera, 42 Bemisia tabaci 43 and Tuta absoluta 44 resulted in significant insect mortality.…”
Section: Discussionmentioning
confidence: 98%
“…Consistent with the central role of dsRNA in triggering RNAi, numerous studies have shown that plants treated with virus‐specific dsRNA or single‐stranded RNA (ssRNA) molecules that fold into hairpin conformation showed antiviral resistance (Carbonell et al ., ; Gan et al ., ; Konakalla et al ., ; Tenllado and Diaz‐Ruiz, ; Tenllado et al ., ,b; Yin et al ., ). dsRNAs were also shown to be effective against fungi (Koch et al ., ; Wang et al ., , ) and insects (Baum et al ., ; Ghosh et al ., ; Li et al ., ; Luo et al ., ), thus providing important implications for dsRNA‐triggered RNAi as an emerging novel approach for crop protection. RNAi has been deployed for plant protection since it was discovered.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have also shown that insects have dsRNA‐degrading enzymes (dsRNase) that affect interference efficiency. Therefore, inhibition of dsRNase expression is conducive to the success of insect RNAi …”
Section: Discussionmentioning
confidence: 99%